The R.S.E: A global performance tool and a lever of competitiveness of companies, Case of ATM Mobilis - HAMAZ , Tahar; KHENNICHE , Youcef (Journal of Excellence for Economics and Management Research, 2024)
Changes in the economic context have forced companies, when carrying out their activities, to consider their duties towards society. The objective of our study is to highlight the consequences of social involvement on the results and competitiveness of companies. Thus, an in-depth study was carried out within the telephone operator ATM Mobilis to highlight its social and societal commitment. The results obtained demonstrated that the incorporation of CSR into the company’s strategic approach contributed to its overall performance.